Creutzfeldt-Jakob disease in Austria. Issue 2 (August 1996) - Hainfellner, J A; Jellinger, K; Diringer, H; Guentchev, M; Kleinert, R; Pilz, P; Maier, H; Budka, H
Abstract : Between 1969 and 30 September 1995, 79 Austrian patients had Creutzfeldt-Jakob disease (CJD) diagnosed neuropathologically by necropsy or biopsy. The annual incidence has significantly increased in recent years (average 0.18 per million in 1969-85, and 0.67 per million in 1986-94; estimate for 1995: 1.5 per million). Also, the percentage of patients with CJD over 70 years at death increased significantly until 1989 but is since in decline. There is no regional clustering, familial occurrence, or recognised iatrogenic risk. One patient had a 10 year history of intramuscular injection of purified bovine RNA preparation (Regeneresen) from various organs including the brian. The ages at death are symmetrically distributed around the median of 64 years. The median duration of disease is four months. Most patients (76%) died within six months of onset. Retrospectively, 86% of patients fulfilled clinical criteria of probable or possible CJD. Neuropathology showed the classic triad of spongiform change, astrogliosis, and neuronal loss in most cases. Two cases did not show unequivocal tissue alterations, but anti-PrP immunocytochemistry detected PrP deposits also in these cases. It is concluded that the recent rise in incidence of CJD in Austria most likely reflects increased awareness and diagnosis of CJD rather than a real increase. As bovine spongiform encephalopathy (BSE) has not been reported in Austria, the data do not support a link between a rise in incidence of sporadic CJD and BSE.